PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMP KAUTSAR DESA KARANG PUCUNG KECAMATAN WAY SULAN KABUPATEN LAMPUNG SELATAN TAHUN PELAJARAN 2022/2023 - Latifah, RN. Khasanah; Handoko, Cipto; Yasin, Muhammad (UNISAN JURNAL, 2023)
school principals. The principal of a school has the ability to improve the performance of teachers in six different ways: (1) by placing significant emphasis on the enhancement of teachers' existing competencies; (2) by making available adequate financial resources for the enhancement of teachers' professional qualifications; (3) by supervising and guiding teachers in a professional manner; (4) by fostering an organizational culture at the school in which teachers feel at ease; (5) by fostering innovation and advancement at the school; and (6) by offering a variety of rewards for each individual achievement. As a result, it is recommended that school principals collaborate with teachers and other educational stakeholders in a more proactive and creative manner to enhance teachers' performance